»Dobbeltkontrakten« og kunstnerisk ytringsfrihed i L’Impromptu de Versailles af Molière - Kuhlmann, Annelis (Peripeti, 2007)
In her analysis of Molière’s play L’Impromptu de Versailles from 1663, Annelis Kuhlmann explores the nature of the »double contract« between the playwright and his audience. In doing so, she draws attention to the theatricality of the play and its conspicuous staging of reality and fiction.